A Scoping Review on Randomized Controlled Trials Investigating Effects of Breathwork in Women With Breast Cancer - Vinitha Ganesan; Kathryn A. Kaiser; Anjani Allada; Alekhya Puppala; David K. White; Mia Mugavero; Akhila Maruvada; Jade Kyle; Harshitha Gutta; Nusrat Jahan; Keerthi Gogineni; Megan Bell; et al. (Lifestyle Medicine)
ABSTRACT Background Patients with breast cancer experience distress, treatment‐related discomfort, and fear of recurrence from initial diagnosis through survivorship. Aims This study aimed to assess the effects of breathwork interventions on the mental health and quality of life of breast cancer patients and survivors. Methods We searched multiple databases for randomized controlled trials involving breathwork interventions in patients with breast cancer. Results Of the 5909 items screened, 16 studies involving 1726 participants met the inclusion criteria. Breathing interventions included yoga (n = 9), qigong (n = 4), and other breathing techniques (n = 3). We found that the highest average risk of bias was in the randomization process, with challenges in accurately evaluating deviations from intended interventions due to unquantified adherence to at‐home practices, although overall bias in the included studies was generally low. Interventions were prescribed daily or weekly, lasting from 1 week to 2 years. Outcomes included treatment side effects, fatigue, sleep, quality of life, biomarkers (e.g., inflammatory markers), psychosocial factors, anxiety, and depression. Conclusions Although positive outcomes were reported in domains of quality of life and emotional well‐being, null findings were reported for vasomotor symptoms such as hot flashes for breathing interventions. The wide range of interventions and outcomes administered to patients in various phases of the breast cancer care continuum complicates firm conclusions. Recruitment and adherence issues were noted in multiple studies. Future research should use more objective outcome measures, increase accessibility of the intervention (e.g., via telehealth) to improve adherence, and include longer follow‐up periods to evaluate survival and recurrence.